Digital violence among secondary school pupils - Jevtić Radoje B. (Zbornik radova (Univerzitet u Kragujevcu. Pedagoški fakultet u Užicu), 2022)
Today's way of working and living involves the use of many products of new technologies. Many analyses of the influence of modern technologies on people and children emphasize benefits of modern technologies. But there are also some very bad effects of the use of modern technologies that are much less noted. One of the very frequent and very dangerous effects of the use of modern technologies is digital violence (cyberbullying). Increasing use of mobile phones, laptops, computers, the Internet, social networks and the like caused this type of violence to become very frequent, especially among school age children. The constant increase of this type of violence implies serious and detailed strategies for their reduction and elimination. This paper had both scientific and professional goals. The scientific goal of the paper was to identify the presence and exposure extent of digital violence among secondary school pupils. The professional goal was to present the results of the research conducted by a questionnaire as well asto emphasize the importance of such survey of pupils in order to better and more effectively monitor digital violence impact on pupils. The research presented in this paper was conducted by the author of this paper and included pupils from secondary schools in Niš.